Validation of the patient health questionnaire-4 for longitudinal mental health evaluation in elite Para athletes - Meidl, Verena; Dallmann, Petra; Leonhart, Rainer; Bretthauer, Berit; Busch, Aglaja; Kubosch, Eva Johanna; Wrobel, Nina Lisa Marie; Hirschmüller, Anja (PM&R, 2023)
Background Despite the increasing amount of research regarding mental health in elite athletes in recent years, athletes with impairments are hardly represented. Due to this lack of data and the significant need of athlete-specific mental health screening tools, a continuous mental health monitoring program for elite Para athletes was implemented. Objective Validation of the Patient Health Questionnaire-4 (PHQ-4) as a suitable tool for continuous mental health evaluation in elite Para athletes. Design A 43-week prospective observational cohort study. Setting Online questionnaire, provided weekly via web browser and mobile app. Participants Seventy-eight Para athletes preparing for Paralympic Summer and Winter Games. Interventions Not applicable. Main Outcome Measures Weekly PHQ-4 scores, stress level, and mood. Results With a mean weekly response rate of 82.7% (SD = 8.0), 2149 PHQ-4, 2159 stress level and 2153 mood assessments were completed. Mean PHQ-4 score among all participating athletes was 1.2 (SD = 1.8; 95% confidence interval [CI], [1.1-1.3]). Individual weekly scores ranged from 0 to 12 and showed significant floor effects, with 54% of the scores being zero. PHQ-4 scores were significantly higher among female athletes and team sport members (p < .001). Internal consistency of the PHQ-4 was satisfying, Cronbach's α being 0.839. There were significant cross-sectional as well as longitudinal correlations of PHQ-4 and stress level as well as mood values (p < .001). 39.7% of all athletes (n = 31) had at least one positive screen for mental health symptoms. Conclusions The PHQ-4 was shown to be a valid tool for mental health surveillance in elite Para athletes. Significant correlations of the PHQ-4 and stress level as well as mood were shown. High weekly response rates among participating athletes indicated good acceptance of the program. The weekly monitoring allowed for the identification of individual fluctuations and could identify potential athletes at risk for mental health problems when combined with clinical follow-up.